Dynamic Changes in the Proteomic Profile of Mesial Temporal Lobe Epilepsy at Different Disease Stages in an Immature Rat Model - Wu, Liwen; Zhang, Ciliu; Yin, Fei (Protein and Peptide Letters, 2015)
Mesial temporal lobe epilepsy (MTLE) is the most prevalent form of refractory symptomatic epilepsy, most patients with MTLE respond poorly to anti-epileptic drugs (AEDs). The pathophysiological mechanism of MTLE remains unclear, blocking the path to successful prevention and treatment. We know that change in brain plasticity after long epileptic seizures in early childhood can produce long-term effects in the individual. It is a dynamic process, developing from early injuries in the immature brain to chronic epilepsy in adults. However, most MTLE studies are limited to a certain aspect of a certain time, rather than taking the long view of epilepsy as a systematic and chronological disease. In this report, we screened and identified proteins that are differentially expressed in the acute, latent and chronic stages of MTLE in an immature rat model. Proteins were screened by proteomics, and western blot was used to confirm differentially expressed proteins, such as synapsin-1, dynamin-1 and neurogranin, in hippocampi from both rats and humans with MTLE. Our results show that the synaptic dysfunction caused by abnormal expression of synaptic proteins play a critical role in the pathogenesis of chronic MTLE.
Keywords: rat